Employee Engagement in the Creative Industry Sector of North Sumatra: Analyzing Work-Life Balance Stimulants and Perceived Organizational Support - Indajang, Kevin; Andronicus, Melkyory; Sembiring, Lenny Dermawan; Ambarita, Marthin Hutler; Sudirman, Acai (International Journal of Business, Law, and Education, 2024)
Employee engagement in the creative industry in North Sumatra is an important concern, considering the contribution of this sector to the regional and national economy. The creative industry, which is full of innovation and high dynamics, requires competent human resources and a strong emotional attachment and commitment to work. This study analyzes factors influencing employee engagement, especially through the work-life balance and perceived organizational support approaches. Using quantitative research methodology, this study aims to identify the relationship between these two factors and employee engagement in the creative industry sector in North Sumatra. The number of samples used was 210 respondents, as determined by the purposive sampling method. The study's results confirmed that work-life balance and perceived organizational support positively and significantly affect employee engagement. These findings are expected to provide insight for companies in designing more effective and sustainable human resource management strategies, especially in this innovation and creativity-oriented sector.